RANCANG BANGUN APLIKASI PENCARIAN JALUR TERPENDEK MENGGUNAKAN ALGORITMA FLOYD WARSHALL (STUDI KASUS KOTA SINGKAWANG) - Istyanto, Mohammad Hendra (Jurusan Informatika Universitas Tanjungpura, 2014)
There are many tourist place located around Singkawang and make the tourist hard to choose the best route to go to the place that they want. That problem is the background of the writer to make an application that can show the most efficient route to the tourism place with maps view. The algorithm that writer use in this application is floyd warshall algorithm. This algorithm search the shortest route from the position of user to the tourism place that he want to go. The input of this application is the place chosen by user and the output is the shortest route to that place. The data of tourism place are came from Dinas Kebudayaan, Pariwisata, Pemuda dan Olahraga and the data of the distant route are came from Dinas Pekerjaan Umum Singkawang. Based on the research, the writer conclude that the application succeed in applying floyd warshall algorithm to search the shortest route to go to tourism place in Singkawang. In this application, there also a features for showing the location of all tourism place in Singkawang.